Mortality, incidence and seasonality of canine and feline patients treated with tick antiserum in three far North Queensland veterinary clinics from 2000 to 2020. Issue 12 (8th September 2022) - Thomas, RP; Greening, SS; Hill, KE
Abstract : Tick paralysis is a paralysis caused by bites from Ixodes holocyclus, affecting an estimated 10, 000 companion animals in Australia annually. Despite tick antiserum being the cornerstone of treatment, there are no large‐scale general practice studies that examine survival outcomes in tick antiserum‐treated animals. In this retrospective study, clinical records from three far north Queensland general practice veterinary clinics were searched for tick antiserum‐treated canine and feline patients were seen between 2000 and 2020. Patient records were assessed for survival outcomes,  then logistic regression and Bayesian structural time‐series model were used to assess trends in incidence and mortality and the relationship between these and time of year, rainfall, and species. The study included 2019 dog and 953 cat records. When patients with unknown outcomes were removed, canine mortality was 11.8% (213/1799) and feline mortality was 5.3% (46/872). Dogs were found to have 2.41 odds of dying following treatment than cats. August and September had the highest mean number of monthly treatments, and rainfall in the previous 5–8 months was positively correlated with the number of patients treated in each month. The odds of mortality did not vary significantly by month or season, and from 2015 onwards, there was a significant decrease in the proportion of dogs treated by the clinics. Overall, this study provides new information on tick antiserum treatment outcomes in general practice as well as new information on tick paralysis incidence in far north Queensland.